2016
DOI: 10.1016/j.envres.2016.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 3-phenoxybenzoic acid (3-PBA) levels among pregnant women in Mexico City: Distribution and relationships with child neurodevelopment

Abstract: Background In recent years, pyrethroid pesticide use has increased in Mexico, the United States, and elsewhere, resulting in extensive human exposure. There is growing concern that pregnant women may be a particularly vulnerable population, as in utero fetal exposure during critical periods of development could adversely affect long-term neurobehavioral function. Methods We measured maternal urinary 3-phenoxybenzoic acid (3-PBA) concentrations during the third trimester of pregnancy as a measure of in utero … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 45 publications
2
38
1
Order By: Relevance
“…However, studies from China ( Xue et al. 2013 ) and Mexico ( Watkins et al. 2016 ) reported decreases in infant and toddler cognition with even lower levels of maternal pyrethroid metabolites than in the current study (e.g., 3PBA in Mexico vs. in VHEMBE).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…However, studies from China ( Xue et al. 2013 ) and Mexico ( Watkins et al. 2016 ) reported decreases in infant and toddler cognition with even lower levels of maternal pyrethroid metabolites than in the current study (e.g., 3PBA in Mexico vs. in VHEMBE).…”
Section: Discussioncontrasting
confidence: 84%
“…On the other hand, a Chinese study reported the sum of prenatal urinary levels of cis –(2,2-dichlorovinyl)-2,2-dimethylcyclopropane-1-carboxylicacid (DCCA), trans -DCCA, and 3-phenoxybenzoic acid (3PBA) to be associated with lower cognitive scores in 1-y-olds ( Xue et al. 2013 ), and a Mexican study found higher 3PBA levels to be related with lower cognitive scores (BSID) at 2 and 3 y of age ( Watkins et al. 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…An additional limitation is that the pesticide metabolite concentrations were determined by one single spot urine sample collected after overnight fasting. The pesticides are assumed to be rapidly metabolized and excreted from the body within hours to days and substantial within-subject variability has been demonstrated for organophosphate metabolites [60] and to a lesser degree for pyrethroids [61]. Thus, some exposure misclassification is expected but it is unlikely to be dependent on the investigated health outcomes, making it non-differential and tend to bias the effect estimates toward the null.…”
Section: Discussionmentioning
confidence: 99%
“…However, fetuses and infants are particularly susceptible to toxicants. An analysis of published studies shows that prenatal exposure to some pesticides may induce malformations (herbicides) [ 8 10 ], affect fetal growth (herbicides, organophosphorous) [ 11 13 ], or are associated to behavioral disorders (organophosorous, pyrethroids) [ 14 23 ].…”
Section: Introductionmentioning
confidence: 99%